The Dalai Lama and the Emperor of China: A Political History of the Tibetan Institution of Reincarnation, by Peter Schwieger. - Galli, Lucia (Buddhist Studies Review, 2017)
The Dalai Lama and the Emperor of China: A Political History of the Tibetan Institution of Reincarnation, by Peter Schwieger. Columbia University Press, 2015. 352pp. Hb. £50.00. ISBN-13: 978-0231168526. E-book. £50.00. ISBN: 978-0231538602.